Sistem Pendukung Keputusan untuk Penentuan Dosen Pembimbing Skripsi menggunakan Algoritme Winnowing-Weighted Product - Rizka Awaliyah Nurul Putri; Ahmad Afif Supianto; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In order to complete their thesis, students need a supervisor. Thesis supervisor plays an important role as a good facilitator, motivator, and director so that the thesis can be completed and ready to be tested. The inappropriate determination of supervisors can hamper the student's thesis guidance and work process. For this reason, an effective system to reccomend thesis supervisors for students is needed to minimize errors that may occur in the determination of the thesis supervisor. The recommendations given are not only based on personal knowledge, but also consider lecturers' researches, KJFD, majors, quotas, positions, and lecturer workload. The lecturer research data used was obtained from Google Scholar, functional position data was obtained from forlap.risetdikti.go.id, and the department data, quota, and lecturer workload were obtained from the Information Systems Management, IT Infrastructure and Public Relations of Faculty of Computer Science (PSIK). The validation test results show that the system built was in accordance with the requirements defined. The usability test results that utilize the System Usability Scale (SUS) show the system usability level is 90% which means system is in the acceptable category..